Penggunaan Metode Pembelajaran Peta Konsep Untuk Meningkatkan Hasil Belasar IPS dan Karakter Nasionalis Siswa Kelas IV SD Inpres Semangga 1 Merauke - Karlina Wong Lieung; Dewi Puji Rahayu (Universitas Negeri Makassar, 2020)
The problem that occurs in fourth grade students of SD Inpres Semangga 1, Merauke Regency is the importance of improving social studies and the nationalist character of students. This study aims to improve social studies learning outcomes on the beauty of diversity in my country theme and the nationalist character of fourth grade SD Inpres Semangga 1, Merauke Regencies students. This research is a classroom action research. The study was conducted in three cycles with each cycle consisting of planning, action, observation, and reflection. The studies subjects were the fourth grade students of SD Inpres Semangga 1, Merauke Regency. The data used in this study were students, teachers, and observers. Data analysis uses quantitative and qualitative techniques, including data reduction, data presentation, and drawing conclusions. The results of pretest grade IV students used the concept map method of 41.76, increasing in the first cycle of 72.06, second cycle 76.47, and third cycle 80.59. The nationalist character of the students from the first cycle was categorized by 17.65%, increased in the second cycle by 70.59% and in the third cycle was 94.12%.